Antibiotic prescribing patterns in general medical practices in England: Does area matter?. (September 2018) - Mölter, Anna; Belmonte, Miguel; Palin, Victoria; Mistry, Chirag; Sperrin, Matthew; White, Andrew; Welfare, William; Van Staa, Tjeerd
Abstract: Antimicrobial resistance is an important public health concern. As most antibiotics are prescribed in primary care, understanding prescribing patterns in General Medical (GP) practices is vital. The aim of this study was a spatial pattern analysis of antibiotic prescribing rates in GP practices in England and to examine the association of potential clusters with area level socio-economic deprivation. The pattern analysis identified a number of hot and cold spots of antibiotic prescribing, with hot spots predominantly in the North of England. Spatial regression showed that patient catchments of hot spot practices were significantly more deprived than patient catchments of cold spot practices, especially in the domains of income, employment, education and health. This study suggests the presence of area level drivers resulting in clusters of high and low prescribing. Consequently, area level strategies may be needed for antimicrobial stewardship rather than national level strategies. Highlights: Results suggest area level drivers of antibiotic prescribing are present in England. Most hot spots of antibiotic prescribing appear in the North of England. Patient catchments of hot spot practices are more socio-economically deprived. Area level strategies for antimicrobial stewardship are recommended.